Investments in a Combined Energy Network Model: Substitution between Natural Gas And Electricity? - Hannes Weigt; Jan Abrell (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Natural gas plays an important role in the future development of electricity markets as it is the least emission intensive fossil generation option while additionally providing the needed flexibility in plant operation to deal with intermittent renewable generation. As both the electricity and the natural gas market rely on networks, congestion on one market may lead to changes on another. In addition, investments in one market have an impact in the other and may even become substitutes for one another. The objective of this paper is to develop a dynamic model representation of coupled natural gas and electricity network markets to test the potential interaction with respect to investments. The model is tested under simplified conditions as well as for a stylized European network setting. The results indicate that there is a potential for investment-substitution and significant market interactions that warrants the application of coupled models especially with regard to simulations of long term system developments.
Keywords: L94; L95; D92; 330